2017
DOI: 10.1039/c7ra05000c
|View full text |Cite
|
Sign up to set email alerts
|

Tea polyphenols ameliorate hydrogen peroxide- and constant darkness-triggered oxidative stress via modulating the Keap1/Nrf2 transcriptional signaling pathway in HepG2 cells and mice liver

Abstract: Tea polyphenols alleviate oxidative stressviamodulating the Keap1/Nrf2 transcriptional signaling pathway in HepG2 cells and the liver of mice kept in constant darkness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…Moreover, as shown in Figure 2, our results also demonstrated that the overexpression of HO-1 in Hep3B cells attenuated H 2 O 2 -induced ROS generation. These results supported recent studies, suggesting that the upregulation of HO-1 alleviated H 2 O 2 -induced ROS and oxidative injury in HepG2 cells [49,50], although, in this study, we did not determine whether ectopic HO-1 overexpression inhibited the apoptosis of hepatoma cells. Since a recent study indicated that IL-6 drives ROS reduction by increasing Nrf 2, a transcription activator of the HO-1 gene, expression in human islet β-cells [51], further investigations into the role of IL-6-HO-1 crosstalk in hepatoma cells, in terms of ROS synthesis, are warranted.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, as shown in Figure 2, our results also demonstrated that the overexpression of HO-1 in Hep3B cells attenuated H 2 O 2 -induced ROS generation. These results supported recent studies, suggesting that the upregulation of HO-1 alleviated H 2 O 2 -induced ROS and oxidative injury in HepG2 cells [49,50], although, in this study, we did not determine whether ectopic HO-1 overexpression inhibited the apoptosis of hepatoma cells. Since a recent study indicated that IL-6 drives ROS reduction by increasing Nrf 2, a transcription activator of the HO-1 gene, expression in human islet β-cells [51], further investigations into the role of IL-6-HO-1 crosstalk in hepatoma cells, in terms of ROS synthesis, are warranted.…”
Section: Discussionsupporting
confidence: 84%
“…However, pretreatment with different concentrations of PHP could signicantly (P < 0.05) up-regulated the gene expressions of these antioxidant enzymes variously in an obvious concentration-dependent manner, which was similar to the previous reports on antioxidants. 15,34 Particularly, compared with the control group, the cells treated with 1.00 and 2.00 mg mL À1 PHP showed signicant increase in mRNA levels of CAT, which was consistent with the activity of CAT, indicating that PHP had the similar concentration-dependent manner effects on the gene expression of CAT (Fig. 2D).…”
Section: Gene Expression Of Antioxidant Enzymes Nrf2 and Keap1supporting
confidence: 65%
“…This action would be facilitated by increased binding activity of NF-κB DNA ( 163 ), a transcription factor that is activated by ROS and regulates the inflammatory and immune response ( 165 ). Moreover, Qi et al ( 176 ) recently found that the apoptosis triggered by DD extends to the liver due to the oxidative damage caused by the overproduction of ROS after a marked reduction in the mRNA levels of antioxidant enzymes.…”
Section: Constant Darknessmentioning
confidence: 99%